Rectification of acetylcholine-elicited currents in PC12 pheochromocytoma cells. - Ifune, C K (1990)
The current-voltage (I-V) relationship for acetylcholine-elicited currents in the rat pheochromocytoma cell line PC12 is nonlinear. Two voltage-dependent processes that could account for the whole-cell current rectification were examined, receptor channel gating and single receptor channel permeation. We found that both factors are involved in the rectification of the whole-cell currents. The voltage dependence of channel gating determines the shape of the I-V curve at negative potentials. The single-channel I-V relationship is inwardly rectifying and largely responsible for the characteristic shape of the whole-cell I-V curve at positive potentials. The rectification of the single-channel currents is produced by the voltage-dependent block of outward currents by intracellular Mg2+ ions.